Luc Peire’s Mwinda Mingi (1955): a Belgian abstract painting on the Congo - Vermeulen, Julien (Acta Academica: Critical views on society, culture and politics, 2012)
As a young artist Luc Peire (1916-1994) was influenced by expressionism, but by 1955, when he painted Mwinda Mingi, his work had become predominantly abstract. The Lingala-title suggests this shift may have taken place during his journey in the Congo and critics have often claimed that the painter’s perception of African village life had a decisive impact on his new style. This assumption however requires a profound analysis taking into account the broader context of Belgian colonial art, Peire’s contacts with modernist artists, the circumstances of his isolated life as a painter-in-residence, the gradual development of his abstract idiom and the ambivalent reception of his new work among expatriates and Belgian critics. The catalogue raisonné of his oeuvre mentions 1398 oil paintings, sixty of which have been inspired by Africa.